Watching the Vessels Grow: Establishment of Intravital Microscopy in the Arteriovenous Loop Rat Model - Hessenauer, Maximilian; Vaghela, Ravikumar; Körner, Carolin; Von Horsten, Stephan; Pobel, Christoph; Gage, Daniel; Muller, Claudia; Salehi, Sahar; Horch, Raymund E.; Arkudas, Andreas (Tissue Engineering - Part C: Methods, 2021)
Tissue engineering in reconstructive surgery seeks to generate bioartificial tissue substitutes. The arteriovenous (AV) loop allows the generation of axially vascularized tissue constructs. Cellular mechanisms of this vascularization process are largely unclear. In this study, we developed two different chamber models for intravital microscopy and imaging of the AV loop in the rat. Multiple design variations were implanted and the stability of the chamber and AV loop patency was tested in vivo. Our novel chamber facilitates repetitive observation of the AV loop using fluorescence-enhanced intravital microscopy. This technique can be used for daily evaluation of leukocyte-endothelial cell interactions, vascularization, and tissue formation in the AV loop model on 14 consecutive days. Therefore, our newly developed model for intravital microscopy will provide better understanding of cellular and molecular processes in tissue engineering in the AV loop. Moreover, it supports initiation of the novel approaches for therapeutic applications. Impact statement In the Arteriovenous (AV) loop, axially vascularized tissue can be generated and modified using different tissue engineering approaches. Cellular mechanisms of this vascularization process are largely unclear. We managed to develop an intravital microscopy model for long-term observation of intravascular and perivascular events in the AV loop. Leukocyte-endothelial cell interactions, vascularization, and tissue formation in the AV loop can now be evaluated on a day-to-day basis. This will provide better understanding of cellular and molecular processes happening during tissue engineering within the AV loop.
CRIS-Team WoS Importer:2021-07-09